2014
DOI: 10.1111/inr.12140
|View full text |Cite
|
Sign up to set email alerts
|

Community health nurses' HIV health promotion and education programmes: a qualitative study

Abstract: Three decades of collective experience in providing holistic and multifaceted HIV and AIDS nursing care, education and health promotion by community health nurses have the potential to effect new and existing policies and protocols on HIV community care in Thailand, but more research is required for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, evidence of patient participation in the decision‐making process (Abe, Turale, Klunklin, & Supamanee, 2014; Alexandropoulou, Sourtzi, & Kalokerinou, 2010; Gonzaga et al., 2014; Hernandez & Anderson, 2012; Larsson et al., 2014; Runciman et al., 2006; Van de Glind et al., 2016), planning educational activities (Abe et al., 2014; Alexandropoulou et al., 2010; Gonzaga et al., 2014; Van de Glind et al., 2016), practice of skills or evaluation of skill development (Abe et al., 2014; Alexandropoulou et al., 2010; Larsson et al., 2014; Runciman et al., 2006; Tanda et al., 2017) is limited, highlighting the misalignment between nurses' activities and the Ottawa Charter's proposal for developing individuals' personal skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence of patient participation in the decision‐making process (Abe, Turale, Klunklin, & Supamanee, 2014; Alexandropoulou, Sourtzi, & Kalokerinou, 2010; Gonzaga et al., 2014; Hernandez & Anderson, 2012; Larsson et al., 2014; Runciman et al., 2006; Van de Glind et al., 2016), planning educational activities (Abe et al., 2014; Alexandropoulou et al., 2010; Gonzaga et al., 2014; Van de Glind et al., 2016), practice of skills or evaluation of skill development (Abe et al., 2014; Alexandropoulou et al., 2010; Larsson et al., 2014; Runciman et al., 2006; Tanda et al., 2017) is limited, highlighting the misalignment between nurses' activities and the Ottawa Charter's proposal for developing individuals' personal skills.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the protection of individuals from environmental hazards, many activities, such as vaccination campaigns (Hoekstra et al., 2016; Irvine, 2007; King & Pappas‐Rogich, 2011; Kwatubana, 2018; Richard et al., 2010; Roden, Jarvis, Campbell‐Crofts, & Whitehead, 2016; Samarasinghe et al., 2010; Thompson et al., 2008), disease screening, contact tracing and partner notification to prevent sexually transmitted diseases (Abe et al., 2014; Sannisto & Kosunen, 2009; Thompson et al., 2008), are performed to protect individuals from biological aggression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Physician attitude is also different with regards to their views on assisted dying and dementia, 19 truthfulness to the patient and their family 31 and their perceptions of end of life care. 37 The performance of medical students has been shown to be dependent on their ethnicity and the culture that they are in, with research revealing that in the UK, those who are non-White are more likely to have a lower achievement, although networking factors had a greater impact on grades than ethnicity. 54 Healthcare professionals with a migrant background disclose diverse experiences in the workplace.…”
Section: Cultural Diversity Of Healthcare Professionalsmentioning
confidence: 99%
“…54 Healthcare professionals with a migrant background disclose diverse experiences in the workplace. Some report positive or supportive relationships, 37,55 whilst others report negative, discriminatory and upsetting relationships with their colleagues. 55,56 Leyerzapf et al 57 found that a cultural minority ethnicity of a physician is seen by specialists and heads of departments to possibly cause a delay in the career paths of the students, although they are also seen to participate less in extracurricular activities including doing internships and PhD research which may also impact on their career.…”
Section: Cultural Diversity Of Healthcare Professionalsmentioning
confidence: 99%